Independensi dan Karakteristik Sikap Masyarakat Tentang Isolasi Mandiri Pada Pasien Covid-19 di Desa Teja Timur Pamekasan - Suhendro, Prastomo; Christiana, Elisa; Rahman, Taufiqur; Alfia, Khomisatul (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
The independent attitude that society has towards the emergence of new health problems is still very dominant during the Covid-19 pandemic, this also influences the government's program in implementing the self-isolation model for Covid-19 patients. This research aims to determine people's attitudes towards self-isolation for Covid-19 patients, to prevent the spread of Covid-19. The design used in this research is descriptive by observing and filling out a questionnaire. The sample in this study was 65 respondents and was taken using a non-probability sampling technique, purposive sampling type. The variable in this study was the community's attitude regarding self-isolation in Covid-19 patients. The instrument used was a Likert scale. Data analysis used descriptive analysis. Most people have an unfavorable attitude towards self-isolation for Covid-19 patients. Based on the research results, it can be concluded that the community's attitude regarding self-isolation for Covid-19 patients in Teja Timur Village, Pamekasan, is largely unfavorable, therefore it is necessary to approach respondents and community leaders and provide more intensive counseling. in order to change respondents' attitudes towards self-isolation for Covid-19 patients